Come the revolution : a memoir - Mitchell, Alex (University of New South Wales Press, 2011)
Many know Alex Mitchell as a political journalist. Few know that he was also a revolutionary. This revealing memoir is a rollicking tale of chain-smoking newspapermen, unionists and revolutionaries, crooked cops and corrupt politicians, spies and dictators; made real by the struggles of ordinary working people.